Yuri!!! on ice [videorecording (DVD)] : the complete series - Yamamoto, Sayo (Crunchyroll ; Funimation, 2018)
After suffering a humiliating loss at the Grand Prix Final, Japan's number one skater, Yuri Katsuki, is ready to hang up his skates for good. But when his idol and five-time champion Victor Nikiforov offers to be his coach, Yuri's put on a trek for gold and to discover the true meaning of victory. Together, they'll face skaters from all around the world while discovering where their true feelings lie.